ANALYSIS OF THE IMPACT OF PENALTY POLICY AS AN INSTITUTIONAL INSTRUMENT OF THE BUDUK VILLAGE WASTE BANK PROGRAM IN BADUNG REGENCY - Ni Luh Aprilia Tamayanti; I Made Endra Kartika Yudha (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Buduk Village is one of the villages in Mengwi District that actively develops a waste bank program as an alternative solution to waste management issues, especially since the absence of an Integrated Waste Disposal Site (TPST) since 2021. In practice, the waste bank in Buduk Village is operated by cadres from the PKK in each banjar. The problem arises when the level of community participation in depositing waste during each scheduled opening of the waste bank is low, which is often caused by moral hazard. To address this issue, several waste banks in Buduk Village implement a disincentive mechanism in the form of a penalty policy for community members who do not routinely deposit waste. This study uses a quantitative approach with the Mann-Whitney Test to analyze the difference in waste deposit frequency between waste banks that implement and do not implement the penalty policy. The analysis results show a very significant difference, where waste banks with a penalty policy consistently exhibit higher deposit levels (Z = -5.832; p = 0.000). In addition, the Spearman Rho correlation test shows a fairly strong positive relationship between the penalty policy and the frequency of waste deposits by customers (r = 0.6016; p = 0.000), indicating that the more firmly the penalty policy is implemented, the higher the tendency of the community to routinely deposit waste. These findings indicate that the implementation of a disincentive in the form of penalties can serve as an effective instrument to increase community compliance and participation in waste management based on waste banks at the village level.